Analysis of Prospective Elementary School Teachers Perspectives on the Implementation of Ice Breaking in Science Learning - Sri Wayuni Wayuni (MISOOL: Jurnal Pendidikan Dasar, 2024)
Learning is a process that is basically not only to convey material, convey messages, but it is expected that there is interaction between teachers or educators and students. Especially in science learning, where in the process students are expected to find something related to their learning. However, in the learning process sometimes a sense of boredom arises, one way to overcome this is by applying ice braking in the science learning process. Ice breaking is a change of atmosphere, from what was boring, making sleepy, or tense, to be more relaxed, relaxed and fun. But then the question is whether the implementation of ice braking is embraced in science learning, considering that in the process there is a practicum. This study aims to determine the prospective teacher's perspective on whether ice breaking can be implemented in science learning. The method used in this research is a qualitative method with interview techniques. The results obtained are From the results of the study it can be concluded that the perspective of prospective teachers regarding the application of ice braking in science learning is very diverse. However, the average prospective teacher states that ice braking can be applied in science learning, but by paying attention to timeliness as well as student conditions and classroom situations in the learning process. When the situation and conditions are considered conducive, then there is no need for the application of ice braking. Reconsidering in the process of learning ipa is not only done by delivering theory, but also practicum.